Synthesis and characterization of poly-L-lysine grafted SBA-15 using NCA polymerization and click chemistry - Kar, Mrityunjoy; Malvi, Bharmana; Das, Anindita; Panneri, Suyana; Sen Gupta, Sayam (Journal of Materials Chemistry, 2011)
Poly-L-lysine (PLL) grafted ordered mesoporous material was prepared by a combination of NCA polymerization and click chemistry. Large pore SBA-15 with a mesopore diameter of similar to 12 nm was synthesized using a previously reported method. The surface of this SBA-15 material was modified with azidopropyl groups. This ``clickable'' SBA-15 was then reacted with an alkyne terminated poly-L-lysine synthesized by the ring-opening polymerization of 3-cbz-L-lysine NCA with N-TMS propargylamine as the initiator. This procedure allows grafting of a uniform polymer film with a high polymer loading. No appreciable pore blocking was observed upon grafting of PLL. No change in the periodic structure of the SBA-15 was observed throughout the grafting process. The SBA-15 PLL conjugate was characterized using (13)C and (29)Si NMR, XRD, FT-IR, N(2) adsorption-desorption and thermogravimetry. The results indicate that polypeptides can be easily grafted onto various ordered mesoporous materials by this ``grafting to'' methodology with accessible pores and high loadings of the polypeptide.

Synthesis of poly-L-glutamic acid grafted silica nanoparticles and their assembly into macroporous structures - Kar, Mrityunjoy; Pauline, Minois; Sharma, Kamendra; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Langmuir, 2011)
Polypeptide-coated silica nanoparticles represent an interesting class of organic inorganic hybrids since the ordered secondary structure of the polypeptide grafts imparts functional properties to these nanoparticles. The synthesis of a poly-L-glutamic acid (PLGA) silica nanoparticle hybrid by employing N-carboxyanhydride (NCA) polymerization to synthesize the polypeptide chains and Cu catalyzed azide alkyne cycloaddition reaction to graft these chains onto the silica surface is reported. This methodology enables the synthesis of well-defined polypeptide chains that are attached onto the silica surface at high surface densities. The PLGA-silica conjugate particles are well dispersed in water, and have been thoroughly characterized using multinuclear (C-13, Si-29) solid state NMR, thermogravimetric analysis, Fourier transform infrared, dynamic light scattering, and transmission electron microscopy. The pH-dependent reversible aggregation of the PLGA-silica particles, driven by the change in PLGA structure, has also been studied. Preliminary results on the use of aqueous dispersions of silica-PLGA for the preparation of three-dimensional macroporous structures with oriented pores by ice templating methodology are also demonstrated. These macroporous materials, comprising a biocompatible polymer shell covalently attached to rigid inorganic cores, adopts an interesting lamellar structure with fishbone-type architecture.

Poly-L-arginine grafted silica mesoporous nanoparticles for enhanced cellular uptake and their application in DNA delivery and controlled drug release - Kar, Mrityunjoy; Tiwari, Neha; Tiwari, Mitali; Lahiri, Mayurika; Sen Gupta, Sayam (Particle & Particle Systems Characterization, 2013)
Mesoporous silica nanoparticles (MSNs), that are capable of delivering gene and drugs to organisms in an effective and selective way have attracted much attention lately for its potential in the treatment of cancer. However, the successful application of MSNs for delivery of plasmid DNA or drugs requires surface modification of the silica with positively charged functional groups so that it binds to the negatively charged nucleic acids and also helps it penetrate through the cell membrane. We report for the first time the synthesis of a hybrid MSN where the cell penetrating cationic polypeptide poly-L-arginine synthesized by NCA polymerization is grafted onto the external surface of MSN using click chemistry. These poly-L-arginine grafted MSNs show low cytotoxity (85% cell viability at 100 g/mL MSN concentration) and high cellular uptake by both HeLa and A549 (>90%). The poly-L-arginine grafted MSNs were used effectively to deliver mCherry DNA plasmid into cells leading to expression of the protein mCherry inside the cells (transfection efficiency 60%). In contrast, poly-L-arginine grafted non-porous silica nanoparticles were unable to express the protein mCherry inside the cells although their uptake into the cells was as efficient as with poly-L-arginine grafted MSNs. We also show preliminary results to demonstrate that these hybrid MSNs can be used as a delivery vehicle for the anticancer drug Doxorubicin towards cancerous cells HeLa and A549. The biocompatibility of poly-L-arginine and its cell penetrating ability are expected to make these MSN conjugates very useful carriers for the delivery of genes and drugs into cancer cells.

Synthesis and self-assembly of amphiphilic homoglycopolypeptide - Dhaware, Vinita; Shaikh, Ashif Y.; Kar, Mrityunjoy; Hotha, Srinivas; Sen Gupta, Sayam (Langmuir, 2013)
The synthesis of the amphiphilic homoglycopolypeptide was carried out by a combination of NCA polymerization and click chemistry to yield a well-defined Polypeptide having an amphiphilic carbohydrate on its side chain. The amphiphilicity of the carbohydrate was achieved by incorporation of an alkyl chain, at the C-6 position of the carbohydrate thus also rendering the homoglycopolypeptide amphiphilic. The homoglycopolypeptide formed multimicellar aggregates in water above a critical concentration of 0.9 mu M due to phase separation. The multimicellar aggregates were characterized by DLS, TEM, and AFM. It is proposed that hydrophobic interactions of the aliphatic chains at the 6-position of the sugar moieties drives the assembly of these rod-like homoglycopolypeptide into large;spherical aggregates. These multimicellar aggregates encapsulate both hydrophilic as well as hydrophobic dye as was confirmed by confocal microscopy. finally, amphiphilic random polypeptides containing 10% and 20% alpha-D-mannose in addition to glucose containing a, hydrophobic alkyl chain at its 6 position were synthesized by our methodology, and these polymers Were also found to assemble into spherical nanostructures. The spherical assemblies Of amphiphilic random glycopolypeptides containing 10% and 20% mannose were found to be surface bioactive and were found, to interact with the lectin Con-A.

Synthesis of end-functionalized phosphate and phosphonate-polypeptides by ring-opening polymerization of their corresponding N-carboxyanhydride - Das, Soumen; Kar, Mrityunjoy; Sen Gupta, Sayam (Polymer Chemistry, 2013)
Phosphopolypeptides provide an interesting biomimetic analog for phosphorylated proteins that are involved in biomineralization. We have developed a high yielding synthesis of cysteine-based phosphate and phosphonate N-carboxyanhydride (NCA) by using the thiol-ene coupling reaction. These phosphate and phosphonate NCA monomers underwent polymerization using simple primary amine initiators to form well defined homophosphopolypeptides. Using a bifunctional initiator we were able to install a ``clickable'' alkyne or azide group at the end of the polypeptide chain. We were also able to successfully synthesize fully water-soluble phosphonate based polypeptides by hydrolysis of the corresponding phosphonate ester groups in the polypeptide. These water-soluble phosphopolypeptides adopt a random coil conformation at physiological pH.